Children living with an alcoholic parent attitudes, perception of parent role, and coping strategies - Dangoy, Aldrin Jose T.; Jaleco, Joecylda N. (2008.)
This study sought to determine the attitudes, perception of parent role, and coping strategies of children with an alcoholic parent. Six adolescent participants were purposely selected from Binalbagan, Negros Occidental. Questionnaires were used to study the variables under investigation. Results showed that children of alcoholics held positive attitudes toward their alcoholic parent. They believed that alcoholic parents deserve to be treated humanely, and that parental alcolohism is caused by psychological attributes above any other factors. They perceived their mothers as more nurturing, providing, and punishing compared to fathers, who were seen as power figures at home. Problem-focused coping strategy was used dominantly by the participants rather than emotion-focused coping.
Thesis (BA-Psychology)--UP Visayas, Miag-ao, Iloilo
Keywords: Alcoholism